Upaya Peningkatan Pemahaman Masyarakat melalui Edukasi 1000 Hari Pertama Kehidupan dalam pencegahan Stunting di Nagari Latang, Kec. Lubuk Tarok Kab. Sijunjung - Tiva Julian Sagita; Asyifa Dwi Ayshah; Amelia Sepyla Desti; Aji Guncoro; Bhariq Novrada; Dori Yuvenda (STKIP Subang, 2025)
Stunting is a chronic nutritional problem that seriously impacts child growth and development and the quality of future human resources. Stunting prevention needs to be implemented early, particularly during the First 1,000 Days of Life (HPK), the golden period for child growth and development. This study aims to evaluate the effectiveness of education about the First 1,000 Days of Life (HPK) in increasing public understanding and awareness regarding the importance of early stunting prevention. The study was conducted on July 10, 2025, at the Pelita Nagari Latang Early Childhood Education Center (PAUD) in Lubuk Tarok District, Sijunjung Regency, involving pregnant women, breastfeeding mothers, and mothers of toddlers. The research method used a descriptive quantitative approach through education, observation, and questionnaires before and after the activity. The results showed an increase in participants' understanding and awareness of the causes, impacts, and practical steps for stunting prevention, including the importance of exclusive breastfeeding, balanced nutrition, appropriate parenting, and utilization of health services. It can be concluded that education about the First 1,000 Days of Life (HPK) is effective in increasing public understanding and awareness of the importance of early stunting prevention